Pengaruh Transmisi Kebijakan Moneter dalam Mempengaruhi Pertumbuhan Ekonomi di Indonesia - Araminta, Marsa Apta (Universitas Negeri Surabaya, 2023)
Economic growth is two important conditions for the prosperity and welfare of a nation. With sufficient growth, the state can continue development and provide good services to its people. Economic growth that is going well is a form of good economic stabilization. Efforts to maintain economic stability are carried out through certain steps to strengthen the resilience of the domestic economy against various shocks that arise, both from within and from abroad. In supporting more optimal economic stability and creating a strong and anticipatory monetary policy framework, it is necessary to have the right monetary policy in achieving stability goals in the long term. Monetary policy transmission is a complex issue, because many factors are involved and influence each other on objectives. end of a monetary policy. Planning in a monetary system will be implemented in the right directions, in accordance with the objectives of a monetary policy. In the financial sector, monetary policy will influence the development of interest rates and the money supply. Meanwhile, in the real sector monetary policy will affect gross domestic product and inflation.